The Bee Hive At Work: Exploring its Searching and Optimizing Potential - Navrat, Pavol; Ezzeddine, Anna Bou; Jastrzembska, Lucia; Jelinek, Tomas (INFOCOMP Journal of Computer Science, 2012)
A model of the bee hive that clearly separates the self-organizing decision-making behaviour of the beesin the hive andthe problem-specific behaviour of the bees outsidethe hive is presented. This separation allows for the applications of the model for different problem domains. The Bee Hiveat Work model has been applied to several problem domains. Results of the application to three problem domains are presented - web search, function optimization and hierarchical optimization. In web search, the model has been successful in following a story as it was developing on web sites. Another its application was able to find global optima of various mathematical functions. We explored also to some extent a rather novel idea of building a hierarchical hive.